2012
DOI: 10.2350/12-03-1172-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Umbilical Cord Coiling Index with Segmental versus Total Length Assessment

Abstract: The umbilical cord is the only communication between the fetus and the placenta and, not surprisingly, lesions or conditions affecting it may have detrimental effects in both. One important feature of the umbilical cord is its coiling index (UCI), with hypo- and hypercoiling being associated with fetal thrombotic vasculopathy, intolerance of labor, intrauterine growth restriction, cord stricture, thrombosis of cord and chorionic blood vessels, and fetal demise. It is essential that every placenta report includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…We included some cases with a cord segment of less than 10 cm. 36 Both of these factors were limitations in our study. Hypocoiled cords have been associated with meconium staining, parity interventions, low Apgar score, fetal pH alterations and chromosomal abnormalities, 14,22,37 and with possible need for neonatal intervention.…”
Section: Discussionmentioning
confidence: 86%
“…We included some cases with a cord segment of less than 10 cm. 36 Both of these factors were limitations in our study. Hypocoiled cords have been associated with meconium staining, parity interventions, low Apgar score, fetal pH alterations and chromosomal abnormalities, 14,22,37 and with possible need for neonatal intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Peres and Taylor showed that shrinkage after formalin fixation and segmental measurement of the umbilical cords (as in our investigation) may result in an overestimation of the UCI. 19 For this reason, we chose a high cutoff level for determination of hypercoiling in our study group rendering better reproducibility. Segemental investigation of the umbilical cords was performed because many placentas are not sent with the whole umbilical cord for pathological investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The association in our case of MFI with a hypercoiled umbilical cord containing a single artery prompted us to consider whether this was just a chance association or whether a mechanism could be envisioned in which these cord abnormalities might be linked to MFI. Umbilical cord coiling can be sonographically demonstrated by as early as 10 weeks of gestation [16]. The number of coils along the cord (umbilical coiling index) has a mean r The embedded chorionic villi show persistence of villous stromal cells and villous outlines (hematoxylin and eosin, original magnification 3200).…”
Section: Discussionmentioning
confidence: 99%